(3OQGSGJ aj GdEbJUGO GdOhdj (B:s (3BQGA GbJUGOjI hGLJeGYjI (B/s - (3GdYHhO, YHO GdCejQ QMjeIs ((3YeGf(B: s (3OGQ OLdI fGTQhf hehRYhf(B, s, 2011)
(3MQH GdYedGJ eXGgQgG hJWhQgG aj Xd GdJMhdGJ aj GdfXGe GdfbOj GdOhdj(B- (3CReI GdfbO GdOhdj aj GdfXGe GdQCSeGdjs
Keywords: (3GdEbJUGOs; (3GdEbJUGO GdOhdjs; (3OQGSGJ(B- (3GdEbJUGO GdOhdjs